IMPLIKASI KEBIJAKAN PEMUNGUTAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) SEBAGAI PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN BADUNG, PROPINSI BALI - Noor Rahardjo, Henny Juliani, Ni Putu Diah Ratih Nareswari Putri, (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
In order to carry out development activities and governance of a country requires considerable financial resources. Taxes are the largest source of funding of Indonesia based management is divided into central tax and local tax. accommodated by the local tax Statute number 28 Year 2009 on Regional Taxes and Levies (PDRD). One of the local tax set out in the act is Bea Acquisition Rights to Land and Buildings (BPHTB). Prior to the enactment of PDRD statute, is a type of tax BPHTB center management is sharing between the central and local governments. However, the Act PDRD set BPHTB as tax policy areas managed by the district / city, and will directly affect the revenue (PAD). One of the areas that carry out those instructions are Badung through regional regulation 14 Year 2010 About BPHTB. The problem studied is how the voting policy BPHTB in Badung regency, and how the policy implications of the PAD BPHTB Badung regency. In legal research, the researcher uses normative juridical approach and evaluative quantitative analysis on the problem first. Using empirical and juridical methods of descriptive quantitative analysis on both issues. The survey results revealed that under Regulation BPHTB Badung implement tariff in accordance with the instructions of the Act PDRD. Badung regency also organize more technical details about the collection BPHTB BPHTB through legislation. Based on the data obtained, there is a significant increase in revenue after the policies of the Act BPHTB PDRD, which almost reached 100%. The increase was menandkan the implications of the adoption of policies to PAD BPHTB Badung regency, Bali. In principle, the policy BPHTB positive impact of fiscal decentralization districts / cities. Thus the district / city governments concerned have an obligation to optimize the potential BPHTB in the region by conducting outreach to taxpayers, and enhances the performance of local officials in terms of service and quality.